Adsorption of EDTA onto calcium oxalate monohydrate. Issue 105 (13th October 2015) - He, Junbin; Lin, Rihui; Li, He; Long, Han; Xuan, Jincai; He, Chaohong; Lan, Yurong
Abstract : Effects of contact time (A) and temperature (B) for the adsorption of EDTA onto CaOx monohydrate crystals. Abstract : Adsorption of EDTA onto calcium oxalate monohydrate crystals was investigated and the adsorption characteristics were analyzed. Experiments were carried out to study the effects of factors such as contact time, initial concentration of EDTA, temperature and solution pH on EDTA adsorption. The experimental results showed that EDTA adsorption on calcium oxalate monohydrate crystals increased with its initial concentration in the aqueous solutions. A high temperature was beneficial to the adsorption process. However, the adsorption capacity of EDTA on calcium oxalate monohydrate crystals decreased as the pH increased from 5 to 8. The kinetic data fitting analysis suggested a pseudo-second-order kinetic model best described the adsorption process. The adsorption equilibrium data analysis indicated that the Langmuir isotherm model fit better than the Freundlich isotherm model, based on the R 2, RMSE and χ 2 values. Thermodynamic parameters such as Δ G 0, Δ H 0 and Δ S 0 for EDTA adsorption have also been estimated. The results demonstrated that nature of the adsorption was feasible, spontaneous and endothermic. This study would provide a foundation for the modification of an oxalate-degrading enzyme using EDTA or its derivatives, in order to endow the enzyme with the adsorption ability of calcium oxalate stones.